Assessment of grain iron and zinc content in diverse wheat accessions under drought and heat stress: Grain Iron and Zinc in Wheat Under Stress - Sheoran, Seema; Mehla, Sawan Kumar; Sonu; Mishra, Chandra Nath; Tyagi, B S; Sareen, Sindhu (Journal of Cereal Research, 2025)
Wheat is an important staple foodgrain that acts as a primary source of dietary energy, and essential micronutrients. Thus, it is crucial to detect potential wheat genotypes that can act as donors for wheat biofortification to enhance nutritional values. The goal of current study was to evaluate a set of 155 diverse wheat genotypes, including wild relatives, synthetic hexaploid wheats (SHWs) and cultivated varieties for grain iron (Fe) and zinc (Zn) contents under normal as well as stress (drought, heat, and combined stressed) conditions. The findings revealed significant genotypic variation for grain Fe and Zn contents, indicating the presence of exploitable genetic diversity under drought and heat stressed conditions. The wild species such as Aegilops peregrina and Ae. tauschii exhibited comparatively higher Fe and Zn content than cultivated and SHWs signifying their potential as valuable genetic resources in breeding programs. Correlation analysis revealed significant positive association of Fe and Zn under all the conditions, suggesting the potential for concurrent breeding improvement. The genotypes viz., PI 603931, PI 604176, and accession 14336 were higher in grain Fe and Zn content under both drought and heat stress, while PI 603931 was identified as most stable genotype across the environments. The identified genotypes could be used as potential donor parents for Fe and Zn in future wheat biofortification programs. This study highlights the possibility of using wheat genetic variation for Fe and Zn enrichment, promoting nutritional security, and preventing hidden hunger.